HUAORANI PEACE (Duke University Press, 2015)
Twenty "uncontacted" Taromenani were slaughtered and two female children kidnapped in retaliation for the spearing of a couple of "civilized" Huaorani in March 2013. After months of indecision, the government of Ecuador decided to abduct the two little captives and send six warriors to jail for genocide. Each of these actions caused a moral outrage locally, nationally, and internationally. This article explores the complex constructions through which these violent events have come to be understood, both by the Huaorani and by Ecuadorian nationals, and it shows how two broad concerns-"territoriality" and "compensation"-have structured both the violent conflicts discussed and subsequent attempts at peace restoration. The essay concludes with a brief anthropological discussion of the relationship between ontology and politics. Whereas recent theorizations of Amazonian cosmic economies of alterity sharpen our understanding of "the assimilation of the Other as a mode of reproduction," they tend to obscure the whys and the hows of intra- and intercultural disagreements, as well as the nature of the resort to violence as a way of asserting one's will.